Monitoring and Watering System for Indoor Gardening using Internet of Things (IoT) - Zulkiffli, Nafisah; Ismail, Nurulhuda; Tukiran, Zarina (Evolution in Electrical and Electronic Engineering, 2021)
The monitoring and watering system for indoor gardening using the internet of things (IoT) is introduced in this project as an alternative method to monitor control indoor gardening remotely. It can help people in their daily routine to ensure that their plants get enough water to grow. This system consists of soil moisture sensor, humidity sensor, ultrasonic sensor, microcontroller, water pump and mobile application. This system's primary purpose is to design a system that monitors soil moisture, humidity, water level and develop an automatic watering system based on the sensor reading. When a soil moisture sensor detects a soil moisture reading that is less than 50% of the threshold level, the water is automatically released. The data is then stored in the Arduino and simultaneously sent to the ThingSpeak through the internet routers ethernet connection. The user can monitor their plants through either web browser or their mobile phone using the Blynk application. Therefore, this project is useful not only to houseplant fans but also can be commercialized to the houseplant industry.